Political Parties and Party Politics - Gyimah-Boadi, E.; Debrah, E. (CDD-Ghana, 2008)
Political parties are widely regarded among the key institutions of modern democracy. In contrast to the Madisonian view that regards parties as ‘sinister interests’ capable of undermining, perverting or usurping the popular will of the majority, contemporary democratic governance is anchored on parties. Indeed, it is difficult to imagine politics without parties in contemporary democratic states. Parties are revered as institutions that bring people together for the purpose of exercising political power within the state: parties are the institutions that provide the linkage between citizens and the political process in democratic polities; party platforms offer the best possible arenas for aggregating diverse interests and passions into coherent system-wide mix of public policies, among others. It is against this backdrop that this chapter examines the nature and quality of party politics in Ghana’s Fourth Republic, and the contribution they have made or are making towards the economic, social and democratic development in Ghana